Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.18805/ijare.a-4801
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizer responsiveness of short duration improved finger millet genotypes to different levels of NPK fertilizers

Abstract: A field experiment was carried out at Agricultural Research Station, Vizianagaram, during Kharif, 2016 under rainfed conditions to know the fertilizer responsiveness of promising finger millet varieties to graded doses of NPK fertilizers. Twenty treatment combinations were tested in split- plot design with three replications. Experimental results revealed that with 125% RDF grain yield increase was 10%, 27% and 48% higher than 100% RDF, 75% RDF and 50% RDF respectively. Among the finger millet genotypes, grain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 2 publications
7
3
0
Order By: Relevance
“…However, no significant difference in days to 50% flowering was noticed between 100% RDF and 125% RDF. Similar findings were reported by Triveni et al (2018). 125% RDF recorded an increase of 10.1% in plant height, 34.5% in productive tillers per plant, 18.4% in fingers per ear, 9.1% in earhead length respectively over 75% RDF; however it was on par with 100% RDF.…”
Section: Resultssupporting
confidence: 88%
“…However, no significant difference in days to 50% flowering was noticed between 100% RDF and 125% RDF. Similar findings were reported by Triveni et al (2018). 125% RDF recorded an increase of 10.1% in plant height, 34.5% in productive tillers per plant, 18.4% in fingers per ear, 9.1% in earhead length respectively over 75% RDF; however it was on par with 100% RDF.…”
Section: Resultssupporting
confidence: 88%
“…Among different NPK fertilizer doses, highest grain yield was recorded in 125% RDF which was 233.9%, 31.1%, 13.2% higher than absolute control, 75% RDF and 100% RDF respectively (Table 1). These results are in conformity with the results reported by Triveni et al (2018). In a long term fertilizer trial at Bengaluru, it was proved that application of N:P2O5:K2O at 50:50:25 kg ha −1 increased finger millet yield and soil fertility status compared tonon-fertilized plants (Sankar et al,2011) [5] .…”
Section: Effect On Yield and Economicssupporting
confidence: 91%
“…These improved varieties of finger millet responded well to the applied fertilizers/manures and resulted in better yields. Similarly, earlier studies also reported differential response in terms of growth and yield attributes of finger millet varieties to different fertilizer doses ( 25 , 26 ). It is evident that the yield differences between varieties was mainly due to their genetic potential and also due to higher tillers, ears m −2 and fingers ear head −1 .…”
Section: Discussionsupporting
confidence: 58%